N1- and C6-substituted adenines : a regioselective and efficient synthesis - Senhorães, Nádia (2013)
New and efficient methods for the synthesis of N1-substituted and C6-substitued adenines were developed from the easily accessible 5-aminoimidazole-4-carboxamidines. Condensation of these compounds with triethyl orthoformate led to the selective synthesis of the N1-substituted adenines. Regioselective preparation of C6-substituted adenines could be accomplished when the same precursors were combined with dimethylformamide diethyl acetal. These C6-substituted adenines could also be obtained from the N1-substituted adenines by Dimroth rearrangement in the presence of dimethyl amine.